Comparative Study of Al2O3 Nanofluid Heat Pipes Using Various Inclinations with Water Based Heat Pipes - Hinge, Hrishikesh; Dhokane, N. T.; Barhatte, S. H. (Asian Review of Mechanical Engineering, 2017)
An experimental study is carried out in order to quantify the net heat transfer from evaporator region of a heat pipe to the cold water poured inside cooling water pot mounted on the condenser end of the heat pipe. For this purpose a setup is designed in order to accommodate five heat pipes out of which four of them are charged with nanofluid in the increasing order such that the concentrations by the total volume of working fluid were 0.1%, 0.3%, 0.6% and 1% respectively and remaining one consisting pure water. For preparation of nanofluids water is used as the base fluid because of its reliability to high temperature and ease of availability. Nanoparticles of the size of 100nm were manufactured in nanolabs and TEM (Transmission Electron Microscopy) analysis is carried out. 20 RTDs (4 RTDs for each heat pipe) were used to measure the local wall temperature; five heaters are mounted at the bottom of heat pipe to heat the evaporator region of heat pipe, and a control panel consisting of temperature indicator, voltmeter and ammeter. A heat input in the steps of 25W is given to the evaporator and the performance is monitored for various concentrations by varying inclinations of heat pipes with respect to horizontal. The tests are stopped after a heat input of 100W. All the tried inclinations (30⁰,45⁰,60⁰,90⁰) proved that there is increase in the net heat transfer rate when heat pipes are charged with nanofluids than that of water.